Współdziałanie organów administracji publicznej a decyzje zależne na przykładzie unormowań dotyczących planu ruchu zakładu górniczego - Szewczyk, Ewa (Wydawnictwo Naukowe UAM, 2019)
The aim of the article is to draw attention to the changes that have occurred in the regulations governing the mining plant operation plan, as a consequence of which such a document is no longer issued in the wording of 2018 on the mode of cooperation between the authorities regulated in Article 106 of the Act of 14 June 1960. – the Code of Administrative Procedure. Mineral deposits are a non-renewable, natural national resource. They should be extracted in accordance with the provisions of the relevant generally applicable law. Their extraction cannot be regarded only in relation to the territory of Silesia and the mines located there. Exploitation of minerals is an activity with a very wide range of occurrence and concerns not only the extraction of coal, but also sands, gravels and aggregates. When it comes to the provisions of the Act: Geological and Mining Law, there is much controversy as to whether this operation plan is being approved in the mode of the authorities co-operating with one another, or – in the light of current solutions – outside it. This paper explains the above controversies and shows that the decision on the approval of a mining plant operation plan is a dependent decision, proceeded however by a decision of a city mayor, or head of a village, issued in a completely separate proceeding, dealing with a different subject, not regulated in Article 106 of the Code of Administrative Procedure.
Co-operation of public administration bodies vs. dependent decisions on the example of regulations governing the mining plant operation plan
Keywords: administrative decision; dependent decision; cooperation mode; mining plant operation plan